Early childhood education nationalist exploration: Implementation of the project to strengthen the profile of Pancasila students (P5) - Alfia Wardatus Soleha; Siti Hamidahtur Rofiah (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
The Project for Strengthening the Profile of Pancasila Students (P5) in PAUD institutions is very worthy of study. One of them is through making ecoladrillo. This research explores the implementation of the Pancasila (P5) Student Profile Strengthening Project in PAUD institutions through ecoladdrilo creations. This study focuses on escalating the implementation of the P5 project at the Raudlatul Athfal Institute, focusing on developing character and Pancasila values in students. This research method is qualitative with a phenomenological approach. Meanwhile, this type of research is field research. The data collection techniques used were interviews, observation and documentation. The data analysis used in this research was Miles and Huberman's data analysis. The results of this research are the steps in implementing the Project for Strengthening the Profile of Pancasila Students (P5) through the Creation of Ecoladrillo, which include: 1. Planning, including Project Planning, Teacher Training, and Collection of Raw Materials; 2. Implementation/Execution: Education on Pancasila Values, Introduction to the Ecoladrillo Concept, Collection of Materials, Making Ecoladrillo; 3. Evaluation includes student participation, environmental impact, understanding of Pancasila values, community response, usefulness, and sustainability. The supporting and inhibiting factors in implementing the Project for Strengthening the Pancasila Student Profile (P5) through the creation of an Ecoladrillo at RA Bustanul Ulum Bulugading Jember are Supporting Factors, including Commitment from RA Bustanul Ulum Bulugading Jember, Student Participation, Parental Involvement, Value Education -Pancasila values, integration of learning Pancasila values. Meanwhile, inhibiting factors include limited resources, technical difficulties, low environmental awareness, and limited space and infrastructure.